Developmentof problem solving abilities of grades 5–8 at Kangaroo summer camp - Kašuba, Romualdas; Rudalevičienė, Regina (Lietuvos matematikos rinkinys, 2013)
In the presented article some problems especially suitable for useful solution on Kangaroo summer camps are presented and discussed.